جهود الشيخ زروق الفاسي في إصلاح التصوف من خلال كتابه _قواعد التصوف_ - يوسف, نجود (University of eloued جامعة الوادي, 2021)
" تعالج هذه الدراسة جهود الشيخ زروق الفاسي في إصلاح التصوف من خلال كتابه_ قواعد التصوف_ و ذلك من خلال استنادي لبعض قواعده و الذي تناول في كثير من القواعد ما يجب أن يتخذها السالك الصحيح للتصوف. وهو موضوع في غاية الأهمية لارتباطه بالواقع الإنساني الصوفي وكل مؤمن على العموم لإن قواعده جاءت متنوعة و متناولة و شاملة عدة مواضيع من عقيدة و أخلاق و التربية و السلوك....وقد وظفت في اشتغالنا على هذا الموضوع منهجا استقرائيا عمدت من خلاله إلى تتبع و استقراء على أهم جزئيات من هاته القواعد واستنباط ما أمكن استنباطه من نتائج، لنخلص في الأخير إلى أن جهود الشيخ زروق بارزة في إصلاح التصوف و بشكل كبير كما يعد علم من أعلام التصوف في المغرب كما أبرز أن للتصوف لما له من أهمية و آثار في تصحيح سلوك المسلم. This study deals with the efforts of Sheikh Zarrouk Al-Fassi in reforming Sufism through his book - The Rules of Sufism - through my reliance on some of its rules, which dealt with many rules for what the correct leader of Sufism should take. It is a topic of great importance due to its connection with the inner human reality and every believer in general, because its rules were varied and covered and included several topics of faith, morals, education and behavior .... We employed in our work on this subject an inductive approach through which I proceeded to follow and extrapolate the most important parts of these rules and elicit Possible conclusions, to conclude that Sheikh Zarrouk's efforts are notable in the reform of Sufism, and significantly, as considered. One of Sufism's flags in Morocco, where he highlighted that Sufism is important and influences in correcting Muslim behavior
عقيدة
Keywords: لجهود- التربية - التصوف; Efforts - Education - Sufism